Methodology to Establish Seed Production Area for Improved Seeds in Pinus kesiya - Kumar, Ashok; Matharoo, A. K. (Indian Forester, 2003)
A Seed Production Area (SPA) of Pinus kesiya was established in the State of Manipur. Detailed description of the methodology, and the gain achieved after culling of the inferior trees are presented. The population retained in the SPA improved by 32.05,20.80,14.66 and 24.15 per cent, respectively, for average index value, height, clear bole height and girth and breast height.